Pengembangan Sistem Penentuan Prioritas Revisi Kriteria Akreditasi Prodi IAPS 4.0 dengan Metode Analytic Hierarchy Process di IAIN Kediri - Ahmad Syamsudin (Jurnal Informatika Universitas Pamulang, 2022)
Good campus management or good university governance (GUG) is a mission written in the statutes of IAIN Kediri. This is because with GUG campus management can be carried out better, the implementation is more transparent and accountable. The preparation of study program accreditation forms is the responsibility of UPPS (Study Program Management Unit) which involves related parties and requires robust and complete data for filling out accreditation forms. UPPS formed an accreditation team to prepare data for filling out forms. The current condition of the study program can be a benchmark in determining the priority of accreditation standards that need to be addressed or improved. The conditions of different study programs make revision priorities different from one study program to another. The Decision Support System (DSS) can be used as a means to assist the accreditation team in setting priorities for the revision of accreditation standards. The AHP method as one of the DSS methods has a good ability to determine the weight of the criteria. The results of this study indicate that this decision support system can provide recommendations in the form of priority order for improving the accreditation criteria for the Mathematics Major. The results of functional testing using black-box testing show that the system is running well in accordance with functional requirements. The results of the ranking process analysis show that the percentage results are highly dependent on the weighting of the criteria entered by the respondents and the Head of Major.